Analyzing Translation Methods in the Hidden Figures Movie - Arroihana, Fairuz Zahro; Kurniarahman, Iwan (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2024)
This study aimed to analyze the translation methods used in the Indonesian subtitles of the movie Hidden Figures based on Newmark’s framework. Employing a mix method, the study identified the application of Newmark’s eight translation methods: word-for-word, literal, faithful, semantic, adaptation, free, idiomatic, and communicative translation. The analysis revealed that all eight methods are present in the subtitles, with the communicative and literal translation methods dominating. Communicative translation accounts for 48.56% (271 occurrences) of the translation strategies used. This translation method conveys a clear and natural message to the target audience. Literal translation accounted for 22.75% (127 times). This translation method follows the source language text while maintaining the grammatical structure of the target language. The finding suggests that the translator prioritized accessibility and clarity for Indonesian viewers while balancing fidelity to the source text with naturalness in translation. The study’s findings provide practical insights for language learners on applying translation methods to everyday communication. Communicative translation emphasizes conveying meaning over exact words, helping learners focus on clarity and comprehension in real-life conversations. Literal translation proves useful for accuracy, particularly with technical terms or straightforward statements. This encourages learners to directly translate terms where languages closely align. The minimal use of semantic translation and adaptation suggests learners should apply these methods when dealing with nuanced meanings or cultural differences, ensuring emotional or cultural relevance without losing key ideas. Understanding these methods helps learners adapt to diverse communication contexts effectively. The limitations and suggestions for future research are also presented